The compact dual-band microstrip antenna with the close resonant frequencies ratio - Golovkov, A.A.; Kalinikos, D.A.; Kiselev, B.A.; Pivovarov, I.Yu; Sugak, M.I. (2001 Microwave and Telecommunication Technology I: Conference Proceedings, September 10-14, 2001, Sevastopol, Crimea, Ukraine, 2001)
The paper presents the results of theoretical and experimental investigations of dual-band low-profiled microstrip antennas, operating in the upper side of C-band. The ratio of mean frequencies in both frequency bands is about 1.05-1.1. These antennas can be used in telemetric and communication multichannel systems.